Opinion about Exercises in Water and Lifestyle of Women Attending Aqua Aerobics Classes - Alicja Drohomirecka; Justyna Wojciuszkiewicz (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Aqua aerobics, as one of the modern forms of movement, is becoming more and more popular among the public. The main objectives of this study is to get to know the lifestyle and opinion on the aqua aerobic classes of women participating in this type of activities. According to the authors, people who take part in aqua aerobics classes probably care about their fitness. They should also be aware of the need to lead a healthy lifestyle, because it is one of the most important factors in human health. The study group included 50 participants of aqua aerobics classes in “AQUA STYL” company in Szczecin. Each subject received a questionnaire. It contained 23 questions. Most of the questions related to information about participants and their way of life. The other concerned the opinion about aqua aerobic classes. Most of the respondents answered that they lead a healthy lifestyle. More than 70% of women felt that they follow rather healthy diet. The analysis showed that aqua aerobics gave pleasure to almost all respondents. The benefit of participation in aqua aerobics classes is generally better mood. Despite the large number of people declaring a healthy lifestyle, it is advisable to increase the awareness of the lifelong need for physical activity. As many as 30% of respondents did not know if they lead a healthy lifestyle. There should be greater promotion of healthy behavior. Instructors should know more about the group attending the classes, in order to make the exercises more attractive and effective.